To Evaluate the Utility of RIPASA Scoring System in the Diagnosis of Acute Appendicitis and to Correlate Histopathological Finding with this Scoring System - Feroz Ahmad; Zahur Hussain; Rohit Goel (Dr. Annil Mahajan, 2023)
Background and Aims: Acute appendicitis is one of the most common surgical emergencies encountered by general surgeon. Early diagnosis and management is critical in order to prevent drastic complication. This study was done to analyze the applicability and accuracy of RIPASA scoring in diagnosing acute appendicitis. Methods: This prospective observational study included all the patients above the age of 12 years with clinical feature of acute appendicitis admitted in surgery department. Patients with palpable appendicular lump, appendicular abscess, previous history of urolithiasis and pelvic inflammatory disease were excluded from the study. All the patients were evaluated with complete history taking and clinical examination and subjected to baseline investigation. The patients were subjected to routine baseline investigations including abdominal ultrasonography. We used RIPASA scoring system for all our subject to reach the definitive diagnosis of acute appendicitis. The score has 14 parameters and each parameter is given a numerical value. We classified the patients into four groups according to the score; a) Score <5=Possibility of acute appendicitis is unlikely; b) Score 5-7=Low probability of acute appendicitis; c) Score 7.5-11.0= High probability of acute appendicitis; d) Score >12.0= Definite acute appendicitis. The patients were properly resuscitated before any surgical intervention. Informed written consent was taken and procedure details were explained to the patient and legal attendant. Results: Total of 100 patients was studied. Out of total 100 patients 93 patients (93%) were documented as having appendicitis by histopathology where as 7% of patients had no evidence of appendicitis on histopathology. The sensitivity and specificity of RIPASA scoring system in our study came out to be 92.47% and 86.92% respectively. The positive predictive value and negative predictive values were 86% and 93% respectively. The diagnostic accuracy rate and negative appendectomy rate were 85.56% and 7% respectively. Conclusion: The RIPASA scoring system is easy and simple to apply as majority of the parameters can be obtained from history, clinical examination and few laboratory tests and looked promising when applied to our setting with better sensitivity, specificity, and diagnostic accuracy.